The Coupling Soliton Equations for 3x3 Optical Coupler Characterization - Chotiwattana, W.; Yupapin, P.P.; Rattanathanawan, P. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this research we report the numerical studies of the propagation of soliton pulses in three-core nonlinear fiber with a triangular coupler device. It described in terms of three linearly coupled nonlinear Schodiger equations. The numerical method used the element method base on the Galerkin method. First, we discrete the time domain using quadratic line elements, then we use the iterative techniques to clarify the element position. It is dependent from the half-beat length (Lc). This case Lc = π/3κ, where κ is linear coupling coefficient. The interactive techniques use θ scheme method, when θ =1/2 known as the Crank-Nicolson scheme. In the part of calculation, input fundamental soliton into core 2 and 3 are zeros. A core 1 has shown that the transfer amplitude into core 3 and 2 is observed. Keywords: finite element methods, soliton switching Corresponding author: E-mail: cast@kmitl.ac.th